Effect of Tik-Tok and Leaflet Media in Increasing Adolescents’ Knowledge and Attitude About Reproductive Health - Haninuna, Gilbert Yesaya; Nayoan, Christina Rony; Haba Bunga, Eryc Z (Journal of Public Health for Tropical and Coastal Region, 2023)
Introduction: The lack of information about reproductive health obtained by adolescents can lead to the inability of adolescents to maintain their reproductive health. Media could be used to improve knowledge and attitudes. It is important to deliver health education using attractive media to influence adolescents’ understanding and attitudes about reproductive health. This study employed a new media, Tik-Tok to improve adolescents’ reproductive health knowledge and attitude. This study is aimed to compare the effectiveness of using Tik-Tok and leaflets on increasing adolescents' knowledge and attitudes in East Nusa Tenggara, IndonesiaMethods: This research was a quasi-experimental study, with a "pretest-posttest group design". The study was done on junior high school students in Semau Island. The subjects of this study were 78 students who were divided into two different group interventions, 39  students for Tiktok and 39 students for a leaflet. Data analysis technique using marginal homogeneity test.Results: There was a significant increase in knowledge and attitude among the students after receiving reproduction health education using TikTok (p=0.0001)  and leaflet (p=0.0001). The average increase score in knowledge was 6.05 in the Tik Tok group, while in the leaflet group was 5.7. The Tik-Tok group's average increase in attitude score was 21.05 and the leaflet group's was 17.9. These result showed that both media were useful to deliver reproductive health information for young students, but TikTok had a better results.Conclusion: Schools need to work with the related sectors to improve comprehensive reproductive health education for students and also incorporate new media in delivering health information.